(untitled) (Educational Dimension, 2020)
The article is sanctified to the analysis of problem of forming of digital competence for the students of pedagogical universities. On the basis of analysis of psychological-pedagogical researches and practical experience the didactics model of formation pedagogical universities students’ digital competence was worked out. The structural blocks of model, that in co-operation provide her integrity and functioning, are in-process certain. Destination, theoretical-methodological, semantically-judicial, control-diagnostic and result blocks behave to them. Worked out and the approved didactics model is schematic presentation of the corresponding system of work, that characterizes a hierarchy, sequence, constituents, stages and applied facilities, forms, methods and to interdependence between them and executes orientation, executive and correcting functions in organization of study of pedagogical universities of disciplines of informatics students.